The Langham Private Hotel: an iconic merger of architecture, urbanism, and decoration in Edwardian Newtown - Jacobs, Jamie (Architectural History Aotearoa, 2019)
Completed in 1908, the Langham Private Hotel in Newtown, Wellington - now known as Ashleigh Court - embodied optimism and grand ambition indivisible from its surrounding community. The building was designed to have maximum visual effects on a high-profile triangular site and was conceived during the suburb of Newtown's heady days of rapid and substantial expansion in the decades around the turn-of-the-twentieth century. Located within a precinct composed mainly of two-storey, timber commercial buildings, the three-storey masonry building housing ground-level stores and a hotel far outstripped its neighbours in size, materials, and architectural articulation. The masonry wedge with its continuous façade along two street fronts featuring superbly executed plaster decoration could only impress. This paper will explore how the Langham Private Hotel's excellence in design resulted from an enlightened merger of architecture, siting, and decoration within Newtown's otherwise uniform commercial streetscape. It will consider its relationship to the typology of plastered, masonry commercial buildings that came to define modernity and progress in late-Victorian and Edwardian Wellington. Finally, it will attempt to understand the ambitions and meanings present in its eclectic plaster decoration that would have been evident to contemporaries. In nearly every design dimension, the Langham Private Hotel can be considered an apex of urban design in Edwardian New Zealand.